1999
DOI: 10.1039/a809147a
|View full text |Cite
|
Sign up to set email alerts
|

Pulse radiolysis studies on redox reactions of gallic acid: one electron oxidation of gallic acid by gallic acid–OH adduct

Abstract: Using the pulse radiolysis technique, studies on reactions of 3,4,5-trihydroxybenzoic acid [gallic acid (GA)] with radical species generated in water are reported. At pH 6.8 and 9.7, OH radicals react with GA to give an adduct initially with rate constants of the order of 1 ] 1010 dm3 mol~1 s~1. This adduct then reacts with parent GA molecules with rate constants of the order 5 ] 108 dm3 mol~1 s~1 to give phenoxyl type radical species having absorption maxima in the 350 nm region. At pH 12 and 13.6, OH/O~radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 7 publications
(2 reference statements)
2
43
0
2
Order By: Relevance
“…Among polyphenols, gallic acid (3,4,5-trihydroxybenzoic acid) derivatives are a well-known group of naturally occurring compounds which have been found in many phytomedicines. In recent years, a number of their biological and pharmacological activities have been described resulting in much attention in the development of synthetic gallic acid derivatives [3][4][5][6][7][8][9][10][11]. These compounds have been proved to have various biological properties including neuroprotective, antioxidant [12] and anticancer activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among polyphenols, gallic acid (3,4,5-trihydroxybenzoic acid) derivatives are a well-known group of naturally occurring compounds which have been found in many phytomedicines. In recent years, a number of their biological and pharmacological activities have been described resulting in much attention in the development of synthetic gallic acid derivatives [3][4][5][6][7][8][9][10][11]. These compounds have been proved to have various biological properties including neuroprotective, antioxidant [12] and anticancer activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…The alkyl esters of gallic acid have been reported to possess anticancer, antioxidant ability and neuroprotective effect [10], scavenging free radicals [11], inducing apoptosis of cancer cells [12], inhibiting squalene epoxidase [13], interfering the signal pathways involving extract of dried flowers of Nymphaea stellata and Eucalyptus hybrida by HPTLC [30]. Another study showed use of RP-HPLC method for quantification of GA in Symplocos racemose [31].…”
Section: Synthetic Derivativesmentioning
confidence: 99%
“…The formed cation radical GA •+ (pK a =5.0) turned into neutral radical by deprotonation under our experimental condition. According to the report in literature, 15 the species with absorption at about λ max 310 nm was assigned to the neutral radical arising from deprotonation of cation radical. …”
Section: Methodsmentioning
confidence: 99%
“…15 Richards and Adams 16 have shown that GA is able to repair the tryptophan radical to produce phenoxyl radical. Recently, it was reported that although GA is a free radical scavenger, it may exhibit prooxidant properties under certain conditions.…”
Section: Introductionmentioning
confidence: 99%